2011
DOI: 10.1186/1471-2350-12-102
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of three genome-wide association studies on vWF and FVIII plasma levels

Abstract: BackgroundElevated levels of factor VIII (FVIII) and von Willebrand Factor (vWF) are well-established risk factors for cardiovascular diseases, in particular venous thrombosis. Although high, the heritability of these traits is poorly explained by the genetic factors known so far. The aim of this work was to identify novel single nucleotide polymorphisms (SNPs) that could influence the variability of these traits.MethodsThree independent genome-wide association studies for vWF plasma levels and FVIII activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…The MARTHA study is a collection of 1,542 patients with venous thrombosis (VT) recruited from the Thrombophilia centre of La Timone hospital (Marseille, France) 169,170,171,172 . All subjects had a documented history of VT, were free of chronic diseases, and were free of inherited thrombophilia including: anti-thrombin, protein C and protein S deficiencies and homozygosity for the Factor V Leiden and Factor II G20210A mutations.…”
Section: The Martha Cohortmentioning
confidence: 99%
“…The MARTHA study is a collection of 1,542 patients with venous thrombosis (VT) recruited from the Thrombophilia centre of La Timone hospital (Marseille, France) 169,170,171,172 . All subjects had a documented history of VT, were free of chronic diseases, and were free of inherited thrombophilia including: anti-thrombin, protein C and protein S deficiencies and homozygosity for the Factor V Leiden and Factor II G20210A mutations.…”
Section: The Martha Cohortmentioning
confidence: 99%
“…We found positive associations with rs732505, 19 identified in a combined analysis of two GWAS reports of vWF (Table 3). Furthermore, we replicated vWF associations in ADAMTS13 , (rs4962153, p = 5.54×10 -8 ), OBP2B (rs11244035, p = 2.33 × 10 -6 ), C9orf96 (rs28602591, p = 1.52 × 10 -4 ), and vWF (rs1063856, p =5.26×10 -6 ) 20 (Table 3; a priori Bonferroni corrected significance threshold p = 6.25 × 10 -3 ).…”
Section: Resultsmentioning
confidence: 70%
“…1921 The EuroCLOT study identified this same SNP as associated with vWF, stroke, large vessel, and cardioembolic stroke. 18 Additional ABO SNPs have been associated with vascular outcomes including venous thromboembolism, ischemic stroke, and coronary heart disease (Table 3) (Supplemental Table III) indicating a major role for this gene in the pathophysiology of vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…These two studies have already been extensively described in [5,6,14] for EOVT and in [6,15-17] for MARTHA.…”
Section: Methodsmentioning
confidence: 99%